Contrasting responses of plant and lichen carbon‐based secondary compounds across an elevational gradient. (23rd November 2020) - Asplund, Johan; van Zuijlen, Kristel; Roos, Ruben E.; Birkemoe, Tone; Klanderud, Kari; Lang, Simone I.; Wardle, David A.; Nybakken, Line
Abstract: Vascular plants and lichens often produce a diversity of carbon‐based secondary compounds (CBSCs) to protect them against biotic and abiotic stresses. These compounds play important but often compound‐specific roles in community and ecosystem processes by affecting herbivore and decomposer activity. However, our understanding of what drives community‐level CBSCs among ecosystems or across environmental gradients is limited. We measured concentrations and compositions of CBSCs for all dominant vascular plant and lichen species present across a 500‐m alpine elevational gradient. These measurements were combined with data on species composition and abundance to obtain whole‐community measures of plant and lichen CBSCs across the gradient. At the whole community level, plant CBSCs had the lowest concentrations while lichen CBSCs had the highest concentrations at the highest elevations. Further, plant CBCSs shifted from those associated with herbivore defence towards those protecting against light and oxidative stress as elevation increased, while lichen CBSCs showed the opposite pattern. Synthesis . Our findings that individual compounds show contrasting responses to the same environmental gradient highlight the importance of studying qualitative as well as quantitative changes in CBSCs. Further, the divergent responses between vascular plants and lichens reveal that in systems where both groups are abundant, they need to be considered simultaneously to better understand how future environmental changes may impact on ecosystem‐level processes. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.